The Effect of Solar Radiation on the Performance of Tilted Bifacial Photovoltaics - Luthfi Saepulloh; Udin Komarudin; Rudi Darussalam (The University of Lampung, 2025)
A solar panel technology known as bifacial photovoltaics (PV) allows sunlight to reach both the front and rear of the module. The purpose of this study is to assess how temperature and solar radiation affect tilt-mounted bifacial photovoltaic systems' performance in tropical regions, particularly in Indonesia. The experiment was conducted in an outdoor location in Bandung. The bifacial PV modules were installed a 15˚ tilted angle facing north, with the PV modules positioned 1.2 meters above ground level on an asphalt base. The experiment was conducted under three different weather conditions: sunny, cloudy, and partly cloudy. Based on the experimental results under sunny conditions, the average solar radiation, surface temperature, and PV power generated were 923.8 W/m², 51.1 ℃, and 245.7 W, respectively. Under cloudy conditions, the average solar radiation, surface temperature, and PV power generated were 458.9 W/m², 43.1 °C, and 91 W, respectively. Meanwhile, under partly cloudy conditions, the average solar radiation, surface temperature, and PV power output are 661.6 W/m², 50.2 °C, and 215.8 W, respectively. The highest efficiency was achieved during partly cloudy weather at 15.85%, followed by sunny weather at 11.99%, and the lowest during cloudy weather at 7.73%.